1998
DOI: 10.1021/jo980462j
|View full text |Cite
|
Sign up to set email alerts
|

New Straightforward Synthesis and Characterization of a Unique 1β-Methylcarbapenem Antibiotic Biapenem Bearing a σ-Symmetric Bicyclotriazoliumthio Group as the Pendant Moiety

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Tandem saponification and cyclization16 of 15 using 3M NaOH (aq) in MeOH afforded the bicyclic compound 2S-824 ( 16 ) in 26% yield. Oxidation of 16 with m CPBA17 in CH 2 Cl 2 furnished both 2SO-824 ( 17 ; 26%) and 2SO 2 -824 ( 18 ; 59%).…”
Section: Chemistrymentioning
confidence: 99%
“…Tandem saponification and cyclization16 of 15 using 3M NaOH (aq) in MeOH afforded the bicyclic compound 2S-824 ( 16 ) in 26% yield. Oxidation of 16 with m CPBA17 in CH 2 Cl 2 furnished both 2SO-824 ( 17 ; 26%) and 2SO 2 -824 ( 18 ; 59%).…”
Section: Chemistrymentioning
confidence: 99%
“…interactions have been observed in a large number of organosulfur compounds controlling the conformation of small and large molecules. [1][2][3][4][5][6][7][8][9][10][11][12] Some of these compounds showed the strong bioactivity, and we suggested that the intramolecular nonbonded S · · · X interactions play an important role on the mechanism of several biological effects. 1,2,[6][7][8][9][10][11][12] For example, the clear S · · · O close contact in the complex crystalline structure of carbonic anhydrase I and acetazolamide was recognized.…”
mentioning
confidence: 99%
“…interactions have been observed in a large number of organosulfur compounds controlling the conformation of small and large molecules. [1][2][3][4][5][6][7][8][9][10][11][12] Some of these compounds showed the strong bioactivity, and we suggested that the intramolecular nonbonded S · · · X interactions play an important role on the mechanism of several biological effects.1,2,6-12) For example, the clear S · · · O close contact in the complex crystalline structure of carbonic anhydrase I and acetazolamide was recognized.12) The same nonbonded interaction was observed in the crystalline structure of acyliminothiadiazoline, which has potent angiotensin II receptor antagonistic activity. 6,11) It is estimated that the ring structure consisted of the intramolecular nonbonded S · · · X interactions was more flexible than that of covalent bonding, and this flexibility increased the binding affinity of the active compound to the flexible pocket of the enzyme or the receptor.…”
mentioning
confidence: 99%
“…Carbapenems are well recognized to have broad antibacterial activities, and most of the carbapenem compounds have been developed for parenteral use such as imipenem [1], panipenem [2], meropenem [3], biapenem [4,5], ertapenem [6] and doripenem [7]. The development of oral carbapenems is now expected in the clinical realm because oral administration is advantageous for patients.…”
Section: Introductionmentioning
confidence: 99%